Characteristics and treatment of congenital perineal groove in male patients - Wang, Kai; Pang, Wenbo; Chen, Wei; Zhang, Dan; Wu, Dongyang; Chen, Yajun (Frontiers in Pediatrics, 2023)
Background Congenital perineal groove (CPG) of male patients has rarely been reported before. The purpose of this study was to review our cases and describe their characteristics and treatment. Methods Four male patients diagnosed with CPG were included in this study. Medical records were retrospectively reviewed. Type of CPG and anal position index (API) of the patients were recorded. Follow-up was through outpatient visits. Results Their age ranged from 4 years and 2 months to 10 years and 9 months. Among the four patients, two complained of intermittent CPG mucosal hemorrhage and the other two had mucous secreting and soiling. The API was 0.24, 0.35, 0.36, and 0.40 for each patient, respectively, all represented anterior displacement. Type of CPG for the four patients were all partial, and the sulcus was from the posterior perineum to the edge of anus. Two patients were associated with hydrocele, imperforated anus, and rectoperineal fistula; one patient had left varicocele; the remaining patient had sacrum split. All the patients had no postoperative complication, and during the follow-up period of 5–8 months, no symptoms recurred in the four patients; they all had normal defecation. Conclusions Both genders share the common three characteristics. In addition, shortened perineum with anterior anus, association of perineal malformations, and partial type occurrence are the extra morphological features in male patients. Furthermore, CPG in males are rarely accompanied by urinary tract infection. Favorable prognosis could be reached after operation.